Non-Arteritic Anterior Ischaemic Optic Neuropathy Associated with Optic Nerve Hypoplasia and Elevated Intraocular Pressure - Rathinam, Nithya (Neuroophthalmology, 2020)
A 46-year-old woman with no known past medical history presented with sudden painless visual impairment in the left eye. Ocular examination showed a swollen and hyperaemic left optic disc with a small and crowded right optic disc. Intraocular pressures were moderately elevated. Investigations for underlying ischaemic and inflammatory markers were normal. A diagnosis of left non-arteritic anterior ischaemic optic neuropathy (NAAION) was made, with associated ocular hypertension. On follow-up, NAAION resolved with anti-glaucoma medication and repeat fundus examination confirmed the presence of an underlying hypoplastic disc. The coexistence of optic disc hypoplasia and elevated intraocular pressure may further augment the risk of developing NAAION.